PERAN KEPUASAN KERJA SEBAGAI PEMEDIASI ANTARA MOTIBASI DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI - Gilang Perdana Putra; Machasin Machasin; Daviq Chairilsyah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to identify the effect of Motivation and Workload on Job Satisfaction and Performance in UPTD Puskesmas Kampar Employees. This type of research is quantitative descriptive research.The collection of research data through questionnaires on 73 employees of UPTD Puskesmas Kampar. Data were analyzed using SPSS 26. The results of this study show that Motivation has a positive and significant effect on job satisfaction. Workload has a positive and significant effect on job satisfaction. Motivation has a positive and significant effect on Performance. Workload has a positive and significant effect on Performance. Job Satisfaction has a positive and significant effect. Job satisfaction is a mediator between work motivation and Performance directly.